2008
DOI: 10.1097/mpa.0b013e31815f3933
|View full text |Cite
|
Sign up to set email alerts
|

Small-Interference RNA Gene Knockdown of Pancreatitis-Associated Proteins in Rat Acute Pancreatitis

Abstract: Background-The pancreatitis-associated protein (PAP) family of genes is induced in acute pancreatitis. We have previously demonstrated that antisense mediated gene knockdown of PAP in vivo decreased PAP gene expression and worsened pancreatitis. Here we investigated the effect of a more stable inhibition of PAP using siRNA gene knockdown in vitro and in an in vivo model of experimental pancreatitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
2
5
0
Order By: Relevance
“…They reported consistent residues of GlcNAc(beta 1-6)[Gal(beta 1-3)]GalNAc alpha which ranged in size from four to nine sugar residues [22]. Similarly, variations in PAP migration have been observed in our other in vivo studies [23]. Whether or not the function of Reg or PAP is contingent on differences in glycosylation status is currently unknown.…”
Section: Discussionsupporting
confidence: 52%
“…They reported consistent residues of GlcNAc(beta 1-6)[Gal(beta 1-3)]GalNAc alpha which ranged in size from four to nine sugar residues [22]. Similarly, variations in PAP migration have been observed in our other in vivo studies [23]. Whether or not the function of Reg or PAP is contingent on differences in glycosylation status is currently unknown.…”
Section: Discussionsupporting
confidence: 52%
“…17 Emerging evidence supports that PAP proteins play regulatory roles during the inflammatory process in pancreatitis. 18,19 Such studies showed the protective role of RegIII/PAPs in AP using PAP knockout mice and small interfering RNA knockdown of PAP1 and PAP3 (RegIIIγ). IL-22 was previously shown to up-regulate PAP1 in cultured pancreatic acinar cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Zhang and colleagues37 found that targeted inhibition of gene expression of PAPs by antisense oligodeoxyribonucleotides exacerbates the severity of AP in rats. Furthermore, they also reported that both small interfering RNA (siRNA)-mediated gene knockdown of PAP and administration of anti-Reg1 and anti-PAP2 antibodies worsens sodium taurocholate-induced pancreatitis 38 39. Using PAP/HIP (hepatocarcinoma intestine pancreas) knock-out mice, Gironella and colleagues23 found that PAP/HIP has anti-apoptotic and anti-inflammatory roles in vivo during caerulein-induced pancreatitis.…”
Section: Discussionmentioning
confidence: 99%